2023
DOI: 10.1002/adsu.202300054
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Carbon as a Means of Carbon Management in Roads

Abstract: This paper introduces biocarbon, referred to as biochar, as a novel eco‐friendly and cost‐effective additive to increase interactions among bitumen components while facilitating carbon management in roadway infrastructures. It is hypothesized that functional groups on biochar surfaces enhance interactions between biochar and bitumen constituents. This in turn enhances mechanical properties and durability of asphalt pavements. This study uses biochars derived from six different types of woody biomass and one ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Efficiency improvements, such as reducing demanding batch heating requirements, optimizing pavement designs, and implementing advanced performance-based specifications, could help lower life cycle emissions. 109…”
Section: Environmental and Health Impacts Of Asphalt Vocsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficiency improvements, such as reducing demanding batch heating requirements, optimizing pavement designs, and implementing advanced performance-based specifications, could help lower life cycle emissions. 109…”
Section: Environmental and Health Impacts Of Asphalt Vocsmentioning
confidence: 99%
“…Future climate policy may place increased regulations and carbon pricing on heavy industries, such as asphalt production, if climate targets are to be met. Efficiency improvements, such as reducing demanding batch heating requirements, optimizing pavement designs, and implementing advanced performance-based specifications, could help lower life cycle emissions …”
Section: Environmental and Health Impacts Of Asphalt Vocsmentioning
confidence: 99%
“…Algae-based biochar, especially when modified, can have a high surface area and porosity, making it highly effective for adsorbing pollutants, including heavy metals, dyes, and organic compounds from wastewater 28 , 43 45 . Moreover, it emphasizes that the presence of N-functional groups in algae-based biochar improved its surface chemistry and adsorption capacity 46 . These findings underscore the potential of modified biochar from green algae for efficient adsorption of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the literature have reported PET as an excellent option for upcycling into various beneficial substances, including liquid and gaseous fuels, as well as carbon-based compounds like activated carbon and carbon microspheres [16]. Carbon can be an additive in material synthesis, considering its tunable features and enormous benefits [17,18]. Graphene remains one of the unique carbon derivatives that could be obtained as an upcycled product from PET [19].…”
Section: Introductionmentioning
confidence: 99%